Experimental verification for perceptual and cognitive processing of visual aesthetic experiences. (August 2021) - Wakabayashi, Masahiro; Kitaguchi, Masatoshi; Sato, Hiromichi; Naito, Tomoyuki
Abstract: Theoretical studies suggest that several mechanisms underlie human visual aesthetic experiences: perceptual processing, which has small variability among individuals (shared properties) and strong correlation with image statistics (e.g. color statistics); cognitive processing, which is idiosyncratic and has weak correlation with image statistics; and emotional processing, which determines the affective part of the aesthetic experience. Furthermore, several experimental studies have reported that the visual aesthetic experience can be largely explained by only a few latent factors. However, it is unclear whether the idiosyncrasy and sensitivity to the image statistics of the latent factors from empirical studies are consistent with the multi-stage processing hypothesis from theoretical studies. In the present study, using exploratory factor analysis, we derived three latent factors of visual aesthetic experiences from participants observing landscape paintings and photographs. Then we examined the difference in the idiosyncrasy of the factors and the relationship between the factors and color statistics. We found that there were significant correlations among the color statistics and Factors 1 and 3, which had a small variance of factor scores (low idiosyncrasy), and no or weak correlation among the color statistics and Factor 2, which had a large variance of factor scores (high idiosyncrasy). Our results provide experimental evidence for the perceptual and cognitive processing of visual aesthetic experiences.